2012
DOI: 10.1002/ange.201205126
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Graphene Oxide Can “Lubricate” Ionic Liquids based on Specific Surface Interactions Leading to Improved Low‐Temperature Hypergolic Performance

Abstract: Figure 3. Ignition delay of graphene or r-GO dispersions in [MAT][DCA] versus temperature. Angewandte Chemie 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…265 A later report shows that GO sheets exhibited a better desensitizing effect than C 60 and CNTs. 166 When 2 wt% GO sheets are added, the impact sensitivity of as-prepared HMX decreases from 100% to 10% and the friction sensitivity reduces from 100% to 32%.…”
Section: Stabilization and Desensitization Of Ems By Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…265 A later report shows that GO sheets exhibited a better desensitizing effect than C 60 and CNTs. 166 When 2 wt% GO sheets are added, the impact sensitivity of as-prepared HMX decreases from 100% to 10% and the friction sensitivity reduces from 100% to 32%.…”
Section: Stabilization and Desensitization Of Ems By Cnmsmentioning
confidence: 99%
“…On the one hand, GO and rGO act as space-qualified lubricants, which strongly improve the low-temperature performance of hypergolic ionic liquids by reduction of their viscosity. 166 However, matching the type of graphene to the specific ionic-liquid functionality is very important in achieving the optimum performance. On the other hand, GO and rGO enhance the ignition and burning properties of hypergolic ionic liquids.…”
Section: Ems Based On Go and Rgomentioning
confidence: 99%
“…As a result, they have found potential applications as electrodes for actuators, [282,283] sensors, [284] supercapacitors, [285,286] Because graphene and SWCNTs share very similar physicochemical features, such as the conjugated electronic structure and surface properties, the approach that has been adopted to prepare solubilized CNTs is also extended to graphene. [268,[293][294][295] . [297] Furthermore, the solubility of the IL-functionalized MWCNTs in water and organic solvents could be reversibly switched by anion exchange.…”
Section: Hydrogen-storage Materialsmentioning
confidence: 99%
“…The combination of XPS, IR, and zeta potential results showed that strong interactions exist between boron and ionic liquids, in which a strongly bound layer that is dense enough to protect the boron surfaces from air oxidation exists on the surface of boron nanoparticles 23. In addition, others have demonstrated that the dispersions of graphene or graphene oxide in the hypergolic ionic liquids can significantly depress the viscosities of ionic liquids, thereby leading to improved lower temperature hypergolic performance but with a concomitant small increase in the ignition delay time 24. More interestingly, the type of graphene surface can lead to dramatically different viscosity and ignition behavior.…”
Section: Boron Chemistry: New Opportunity For Hypergolic Ionic Liquidmentioning
confidence: 99%